Urban Noise Restricts Song Frequency Bandwidth and Syllable Diversity in Bananaquits: Increasing Audibility at the Expense of Signal Quality - Winandy, Gabrielle S. M.; Félix, Rafael P.; Sacramento, Rafaela A.; Mascarenhas, Rilquer; Batalha-Filho, Henrique; Japyassú, Hilton F.; Izar, Patrícia; Slabbekoorn, Hans (Frontiers in Ecology and Evolution, 2021)
Anthropogenic noise can interfere with animal behavior through masking of acoustic communication. In response to masking, animals may change their acoustic signals as an apparent adjustment strategy, but this may have a drawback on signal quality. Songs and calls may show noise-dependent changes in frequency and duration, which may yield some masking avoidance, but may also constrain other acoustic parameters that might carry information about the sender. In the present study, we investigated whether noise-dependent reduction in frequency bandwidth or song duration restricted syllable diversity or song elaboration in a Neotropical songbird, the bananaquit (Coereba flaveola). We show that bananaquits sing higher frequency songs, of narrower bandwidth, in noisier territories, independent of variation in territory density, without significant variation in song duration. We also show that songs with higher minimum frequencies, narrower bandwidths, and shorter durations have on average a lower number of syllable types and higher syllable rates.. This finding is in line with an acoustic restriction and may reflect a functional trade-off between audibility and signal value: higher frequencies may be more audible but less elaborate songs may weaken the message of sender quality. Consequently, noise pollution may not only alter avian communities, but also shape acoustic diversity and processes of sexual selection in urban environments.